MENGINTIP PEMBENTUKAN KARAKTER ISLAMI SISWA PADA PERATURAN MADRASAH: MENGINTIP PEMBENTUKAN KARAKTER ISLAMI SISWA PADA PERATURAN MADRASAH - Iqbal, Muhammad (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2022)
Abstract: Madrasa regulations are a value that must be obeyed by every student and educator in an educational institution. The regulation is one of the efforts made by madrasas in the context of forming the character of Islamic students. The formation of student character in madrasas can be applied in the form of routine activities, spontaneous activities, programmed activities, and exemplary activities. Students' rules and regulations applied in madrasas are able to instill student character values through habituation of student activities and are an extension of family education for students. The character building of students is carried out by using the habituation method that is applied from madrasa regulations so that students have an Islamic character. The application of student activities carried out in daily activities at school is a manifestation of Islamic character, such as the habit of praying dhuhur, discipline in attendance at madrasas, short letter muraja'ah, short letter tahfid, and neatly dressed. Keywords: Education, Character, Madrasah Regulations, Islam